2015
DOI: 10.1007/978-3-319-18881-2_2
|View full text |Cite
|
Sign up to set email alerts
|

Damage to Sperm DNA Mediated by Reactive Oxygen Species: Its Impact on Human Reproduction and the Health Trajectory of Offspring

Abstract: Disruptions to the genetic integrity of the mammalian spermatozoon play a major role in determining the subsequent developmental trajectory of the embryo. This chapter examines the causative links that connect DNA damage in human spermatozoa and the appearance of mutations in the progeny responsible for a variety of clinical conditions from autism to cancer. Integral to this discussion is an abundance of evidence indicating that human spermatozoa are vulnerable to free radical attack and the generation of oxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0
7

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(47 citation statements)
references
References 99 publications
(95 reference statements)
0
40
0
7
Order By: Relevance
“…The direct mechanisms by which phthalates may induce these adverse reproductive outcomes are not clear but there is growing evidence that oxidative stress may be a contributing factor. Oxidative stress is implicated in adverse reproductive conditions including sperm DNA damage (Gavriliouk and Aitken, 2015), endometriosis (Mier-Cabrera et al, 2011; Sharma et al, 2010), and polycystic ovary syndrome (Palacio et al, 2006). Additionally, recent evidence suggests strong positive associations between urinary phthalate metabolite concentrations and biomarkers of oxidative stress among pregnant women (Ferguson et al, 2014; Ferguson et al, 2015; Holland et al, 2016), couples who were planning pregnancy (Guo et al, 2014), and the general US population (Ferguson et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The direct mechanisms by which phthalates may induce these adverse reproductive outcomes are not clear but there is growing evidence that oxidative stress may be a contributing factor. Oxidative stress is implicated in adverse reproductive conditions including sperm DNA damage (Gavriliouk and Aitken, 2015), endometriosis (Mier-Cabrera et al, 2011; Sharma et al, 2010), and polycystic ovary syndrome (Palacio et al, 2006). Additionally, recent evidence suggests strong positive associations between urinary phthalate metabolite concentrations and biomarkers of oxidative stress among pregnant women (Ferguson et al, 2014; Ferguson et al, 2015; Holland et al, 2016), couples who were planning pregnancy (Guo et al, 2014), and the general US population (Ferguson et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, it was shown [9] that ROS produced by white blood cells, cause damage of sperm DNA. Although the presence of leukocytes in semen did not diminish the in vitro fertilizing capacity of spermatozoa, the introduction of leukocytes into washed spermpreparationsreducedspermfunctionbyROSproduction [2].Thisfindingseems paradoxic,butitindicatesthatseminalplasmahassignificantantioxidantorROSsca venging capacity which may prevent sperm damage by the leukocytes.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, paternal aging was known to be linked with several adverse clinical conditions including ASD. 42 The study of Lampi et al supports premature birth as a significant risk factor for ASD. 25 In Bangladesh around 13 to 25% babies are reported to born preterm, 44, 45 which is quite high and supports our finding that neurodevelopmental disorder may arise from preterm birth leading ASD.…”
Section: Discussionmentioning
confidence: 97%
“…15 Croen et al found that risk of ASD was increased significantly with each 10 years increase in maternal and paternal age. 14 According to some researchers, the father aged over 35 years 42 and mother aged over 30 or 35 years 1, 21 were suspected as a high-risk condition. This delaying childbearing trend contributes around 4.6% increase in autism over the decade.…”
Section: Discussionmentioning
confidence: 99%